2020
DOI: 10.1101/2020.02.04.933333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunological role of primary cilia of dendritic cells in human skin disease

Abstract: 18Primary cilia are a unique organelle, known to provide a signaling hub for variety of cell 19 activities. Their potential role(s) in human immune homeostasis and diseases, however, have 20 yet to be explored. Here, we show that human dendritic cells (DCs) express primary cilia-like 21 structure. The primary cilia growth during DC proliferation by GM-CSF was shut off by DC 22 maturation agents, suggesting the role of primary cilia to transduce proliferation signaling. 23PDGFRα pathway, one of proliferation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…Langerhans cells are bone-marrow-derived antigenpresenting immune cells located in the basal and suprabasal layer of the epidermis (Lombardi et al, 1993). Langerhans cells have characteristic features of dendritic cells, and the presence of PC in both Langerhans and dendritic cells has been shown (Toriyama et al, 2020). Granulocyte macrophage-colony stimulating factor (GM-CSF) is a hematopoietic growth factor that is mainly produced by immature Langerhans cells and stimulates the formation of PC in granulocytes and macrophages, activating the differentiation of granulocytes and macrophages from bone marrow precursor cells.…”
Section: Langerhans Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Langerhans cells are bone-marrow-derived antigenpresenting immune cells located in the basal and suprabasal layer of the epidermis (Lombardi et al, 1993). Langerhans cells have characteristic features of dendritic cells, and the presence of PC in both Langerhans and dendritic cells has been shown (Toriyama et al, 2020). Granulocyte macrophage-colony stimulating factor (GM-CSF) is a hematopoietic growth factor that is mainly produced by immature Langerhans cells and stimulates the formation of PC in granulocytes and macrophages, activating the differentiation of granulocytes and macrophages from bone marrow precursor cells.…”
Section: Langerhans Cellsmentioning
confidence: 99%
“…Granulocyte macrophage-colony stimulating factor (GM-CSF) is a hematopoietic growth factor that is mainly produced by immature Langerhans cells and stimulates the formation of PC in granulocytes and macrophages, activating the differentiation of granulocytes and macrophages from bone marrow precursor cells. Furthermore, PDGFRα localizes to PC, and PDGFα signaling promotes the proliferation of dendritic cells (Toriyama et al, 2020).…”
Section: Langerhans Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, LCs play an important role in bridging innate immunity and acquired immunity. LCs are present at a rate of about 2–5% in normal epidermis but increase in AD: 13–16% of KCs isolated from AD patients in vitro , and nearly 30% in vivo , were positively stained with a proliferation marker, ki67 ( Czernielewski and Demarchez, 1987 ; Chorro et al, 2009 ; Toriyama et al, 2020 ). The elimination of LCs suppressed the immune response induced by protein antigens ( Nakajima et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to understand the pathophysiology of human inflammatory diseases because mechanisms of inflammatory responses are so complicated, and the immune response between model rodents and humans are usually different ( Beura et al, 2016 ). Recently, we showed that the primary cilium, which acts as a signaling hub, regulates the proliferation, differentiation, and maturation of human KCs and LCs ( Toriyama et al, 2020 ). This review discusses the function of primary cilia, especially inflammatory regulation, in human skin in the context of the literature, and the possible therapeutic potential of targeting signaling pathways transduced in primary cilia.…”
Section: Introductionmentioning
confidence: 99%